Respons terhadap Teori Epistemologi Nonfondasionalisme dan Pengaruhnya di dalam Teologi - Sulistio, Thio Christian (Verbum Christi: Jurnal Teologi Reformed Injili, 2025)
The rise of postmodernism correlated with the emergence of nonfoundationalist epistemology theory. Nonfoundationalist epistemology theory critiques foundationalism, particularly modern classical foundationalism.  In addition to providing a critique, this theory presents a viable option for Christian theology to be recognized as a legitimate epistemological theory for doing Christian theology. Nonetheless, the question of whether we can embrace nonfoundationalist epistemology in our theology comes up.  To respond to this inquiry, the author will examine the shortcomings of modern classical foundationalism, which led to the development of nonfoundationalism as an alternative, using literature research.  The evaluation of nonfoundationalism's perspectives and the theological issues it raises will follow.